Review of the genus Lesteva Latreille, 1797 of Central Asia (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2015)
A taxonomic review of the genus Lesteva Latreille, 1797 of the Central Asia is presented. The type material of the following species was revised: L. bucharica Fauvel, 1900, L. fasciata Luze, 1903, L. nova Bernhauer, 1902, L. transcaspica Bernhauer, 1935 and L. turkestanica Luze, 1904. Lectotypes for L. bucharica and L. turkestanica, a lectotype and paralectotype for L. transcaspica are designated. One species is described as new: L. (s.str.) schuelkei sp. n. (Tajikistan, NW Pamir: Peter-I Mts. and Hissar Mts.). Three synonyms are proposed: L. (s.str.) fasciata = L. (s.str.) turkestanica, syn n. = L. (s.str.) transcaspica, syn. n., L. nova = L. (s.str.) aculeata Shavrin, 2010, syn. n. Three species are redescribed: L. (s.str.) bucharica, L. (s.str.) fasciata and L. (s.str.) nova. All species are illustrated and their distribution mapped. A key to species known from Central Asia, as well as new provincial records for L. (s.str.) barsevskisi Shavrin, 2010, L. (s.str.) bucharica and L. (s.str.) fasciata are provided.